Ethics as usual? Gender differences in work ethic and grades - Harðardóttir, Arna Kristín; Guðjónsson, Sigurður; Minelgaite, Inga; Kristinsson, Kári (Management, 2019)
This research focuses on female work ethics in Iceland, one of the most gender equal countries in the world. The Multidimensional Work Ethic Profile (MWEP) was used for measuring the work ethic of 238 students of both genders. Based on a convenience sample obtained from the School of Business, University of Iceland we tested two hypotheses. The first concerned whether women have a higher work ethic than men; the second whether female students have higher grades than their male counterparts. We found women to have both a higher work ethic and grades than men. Overall outcomes based on the MWEP revealed statistically significant differences between the averages of women and men, with the mean for women higher by 7.07 points. In addition, women’s average university grades were found to be statistically higher than those of men by a margin of 0.36 points. These results provide interesting insights into the potential contribution of women and men to the workplace, suggesting that women, on average, will be more productive and deliver superior performance. Furthermore, work-based research and evaluations are necessary to test this inference, including the research across different sectors of the Icelandic economy.